The Language of Violence against Women: Male Voice Domination in the Public and Private Domains - Fransisca Kristanti (Journal of Language and Literature, 2022)
Violence against women (VAW) has been a long-debated issue for many things, including the authoritative male voice that often reduces (if not diminishes) women’s voice in public and private domains. Often, the lines between the public/private dichotomy become blurred, and the traditional gender perception practiced in the private domain transcends to the public domain. This literature review scrutinizes the authoritative male voice in both the public and private domains within the violence against women discourse. This paper reports that the male authoritative voice is prevalent in both the private and public domains. Yet, the faint lines between the private and public domains cause the interference of a more structural authoritative voice toward the private domain. Even though the language of support enables the victims’ and survivors’ experiences to be verbalized, the support center staff are not all linguistically equipped to effectively elicit and report the experience. This ineffective elicitation and reporting open opportunities for the authoritative male voice to maintain its power in VAW cases.